Employment law for business students - Hardy, Stephen T.; Upex, R. V.; Sage eBooks (London : SAGE, 2006)
Tailored to meet the needs of business students, this book allows readers to navigate the core legal provisions in employment law and get to grips with crucial issues. The language used is easy to follow and the book provides an accessible introduction to the subject in addition to relevant examples.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Labor laws and legislation -- Great Britain; Electronic books